Shadows of political corruption amidst the trend of declining democracy in Indonesia: Learning from the dynamics of 2024 Presidential Election - Ahmad Khoirul Umam (Komisi Pemberantasan Korupsi, 2024)
This conceptual article is based on primary and secondary data from various sources discussing the dynamics of Indonesian politics and democracy through the 2024 General Election. This article aims to identify various alleged political corruption practices as well as to evaluate the development of the quality of Indonesian democracy implied by the 2024 political process. Although allegations of political corruption are believed to be common among many groups, proving them legally and politically is not easy to do. This leaves a number of notes, especially regarding the nature of power and the trend of weakening the quality of democracy in the country. The 2024 General Election provided some valuable lessons that the aspects of neutrality and independence of state power should be of common concern to reorganize and increase the quality of the future Indonesian democracy.